Technical and financial proposal for sustainability of the Copperbelt Environment Project in Zambia - Sinkamba, Peter (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.